2006
DOI: 10.1097/00005721-200611000-00006
|View full text |Cite
|
Sign up to set email alerts
|

How to Implement Complementary Therapies for Laboring Women

Abstract: Complementary therapies have been a part of nursing practice for centuries and are supported today as a part of nursing practice by many state boards of nursing. Some of these modalities can be used by nurses as a part of their comprehensive plan of labor support for women during the childbirth experience. This article describes five complementary therapies (aromatherapy, massage, use of birth balls, music therapy, and hydrotherapy), and how one large Midwestern hospital system implemented an educational progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 20 publications
0
29
0
12
Order By: Relevance
“…These findings also demonstrated that use of the birth ball during labour was safe. [6] Regarding the experience of using the birth ball during labour, most women reported that it could promote comfort and relaxation, reduce their anxiety, as well as labour and back pains. This was consistent with the information in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…These findings also demonstrated that use of the birth ball during labour was safe. [6] Regarding the experience of using the birth ball during labour, most women reported that it could promote comfort and relaxation, reduce their anxiety, as well as labour and back pains. This was consistent with the information in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with recommendations for parturient women's adequate ball use, which should follow some safety precautions. Among these, the presence of a companion for support and safety or of a firm support in front of the parturient, like the bed for example, are fundamental (5) . As for the orientations that have been practiced for ball use, 31.7% of the answers the nurses gave mentioned the propulsion movement, up and down, when sitting on the ball and 30.5% the rotating hip movement.…”
Section: Discussionmentioning
confidence: 99%
“…A bit less frequent (46.9%), pain relief was also mentioned. The movements accomplished when using the ball enhance comfort and can decrease pain by stimulating the mechanic receptors of the pelvic articulation (5) . When asked about difficulties to put in practice ball use during labor care, 25 (80.6%) nurses answered they did not face any problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,23 Doğum eyleminde dilatasyonun gerçekleştiği travay sürecinde kontraksiyonlara bağlı hissedilen ağrı normal ve beklenen bir durum olmakla birlikte, ağrı en şiddetli ağrı kaynağı olarak da bilinmekte ve tanımlanmaktadır. 6,22,[24][25][26][27][28][29][30][31][32][33][34][35] Doğum ağrısı, öznel bir deneyim olması nedeni ile kültürel, bilişsel, dinsel, ruhsal ve çevresel faktörlerden etkilenebilmektedir. 6,36,37 Diğer yandan doğum eyleminde yaşanan korku, gerilim ve ağrı gibi psikomotivasyonel faktörler uterus aktivitesini azaltarak doğum sürecini uzatabilmektedir.…”
unclassified